Abnormally Low HbA1c Caused by Hemolytic Anemia, a Case Report and Literature Review - Sajjad Bakhtiari; Nathan E. Timbrell; Sènan M. D’Almeida (British Journal of Biomedical Science)
Hemoglobin A1c is a widely used diagnostic tool for monitoring glycemic control in diabetes management. However, its accuracy can be influenced by various factors. We present a case of a 17-year-old boy with abnormally low Hemoglobin A1c levels caused by warm autoantibody-induced hemolytic anemia. This case highlights the importance of considering conditions that may affect erythrocyte survival, and the potential interferences when interpreting Hemoglobin A1c results to ensure accurate diagnosis and effective management of diabetes.